Examining host-tourist relationships in research-related tourism - Trupp, Alexander *; Shah, Chetan; Stephenson, M. L. * (2021)
The study examines the perceptions of an indigenous host community in the context of research-related tourism (RRT) in Fiji. A qualitative methodology including interviews and participant observation was adopted for data collection and analysis. The main findings highlight that RRT possesses socio-economic and environmental benefits for the host community, notably increased income, improved infrastructure, perceived livelihood improvement, and the acquisition of knowledge. Negative impacts of RRT were identified regarding to issues of benefit sharing, reciprocity and transparency.